Experimental constraints on germanium diffusivity in metal and silicate phases during core formation of planetesimals and terrestrial planets - Baptiste Le Bellego; Celia Dalou; Béatrice Luais; Pierre Condamine; Vincent Motto-Ros; Laurent Tissandier (Geochimica et Cosmochimica Acta, 2026)

Genesis and fate of incipient melt in shallow lower mantle - Siddharth Khan; Denis Andrault; Pierre Condamine; Federica Schiavi; Jean-Luc Devidal; Nathalie Bolfan-Casanova (Contributions to Mineralogy and Petrology, 2025)

The effect of CO2 on the partitioning of H2O between clinopyroxene and melts and melting of volatile-bearing eclogites - Andrea Curtolo; Pierre Condamine; Federica Schiavi; Nathalie Bolfan-Casanova; Davide Novella (Geochimica et Cosmochimica Acta, 2025)

Generating Spatialised and Seasonal Deep‐Time Palaeoclimatic Information: Integration Into an Environmental‐Dependent Diversification Model - Delphine Tardif; Fabien L. Condamine; Serafin J. R. Streiff; Pierre Sepulchre; Thomas L. P. Couvreur (Global Ecology and Biogeography, 2025)
Aim Testing the impact of climate on diversification is a major goal of evolutionary biology. Birth‐death models like palaeoenvironment‐dependent diversification (PDD) models, for example, allow exploring the potential correlations between diversification dynamics and past environmental changes, such as temperature, among other abiotic variables. So far, such studies have been limited to proxy‐derived global temperature trends, because these are the only temperature records that are easily accessible and almost continuous over multimillion‐year periods. Innovation In this study, we propose a methodology to generate spatialised and/or seasonal palaeotemperature time series. To do so, we take advantage of temperature variables simulated by climate models for several ‘snapshots’ of the last 100 million years. Based on the hypothesis that a long‐term global temperature drift is imprinted, to some degree, on all regional and seasonal temperature records, we use the global proxy‐derived temperature record as the mean of interpolation between discrete climate simulations. We then evaluate the possibility of constraining the PDD models, as implemented in RPANDA, with these hybrid temperature time series. We assess if these regional and seasonal temperature trends may be more relevant to the evolutionary history of a given clade than the global temperature record used so far. Main Conclusions Our results show that PDD models using seasonal and/or regional hybrid temperature time series tend to receive high statistical support. This offers promising perspectives for refining our understanding of the impact of regional and seasonal temperature evolution on diversification dynamics, and calls for continuing development of deep‐time palaeoclimate modelling and interdisciplinary studies.

Seasonal migration and the evolution of an inverse latitudinal diversity gradient in shorebirds - Paul Dufour; Pierre‐André Crochet; Fabien L. Condamine; Sébastien Lavergne (Global Ecology and Biogeography, 2024)
Aim While the evolution of seasonal migration and its association with biogeography have been the subject of numerous studies, its influence on species diversification has rarely been examined. The aim of this study is to explain the atypical latitudinal diversity gradient in shorebirds: did seasonal migration influence diversification and did the gradient evolve from higher in situ diversification or repeated transitions? Location Global. Time Period Palaeogene to present. Major Taxa Studied Order Charadriiformes (shorebirds and allies). Shorebirds include the species with the longest annual migrations in birds and exhibit an inverse latitudinal diversity gradient, with more species breeding toward higher latitudes. Methods We first assessed the temporal and geographical framework of the evolution of migration using a newly reconstructed time‐calibrated phylogeny, and using the fossil record as a complementary source of information. We then used hidden state speciation and extinction models to test whether diversification and thus the latitudinal diversity gradient has been shaped by migratory behaviour or species latitudinal distribution. Results We found that the ancestor of Charadriiformes was likely a tropical year‐round resident and that the current clade's distribution of diversity was not shaped by dispersal events out of the tropics but rather by higher in situ diversification in temperate biomes compared to tropical biomes. Seasonal migration did not affect diversification rate in our models. However, the evolution of seasonal migration seems to be a prerequisite to breed in temperate biomes, indirectly enabling the higher diversification observed in temperate biomes. Main Conclusions Our results bring original insights into how the migratory behaviour acted as a precursor in the diversification and biogeographical history of a large bird clade, ultimately shaping an atypical latitudinal diversity gradient.

The role of the Neotropics as a source of world tetrapod biodiversity - Andrea S. Meseguer; Pierre‐Olivier Antoine; Antoine Fouquet; Frédéric Delsuc; Fabien L. Condamine (Global Ecology and Biogeography, 2020)
Aim The Neotropics currently host outstanding levels of species richness, with one‐third of the global tetrapod species. The underlying causes of these extraordinary levels of biodiversity are a topic debated in evolutionary ecology, but the main processes at work remain elusive. Location Neotropics. Time period Cenozoic and Mesozoic. Major taxa studied Tetrapods. Methods Using global phylogenies for amphibians, birds, lepidosaurs and mammals, biogeographical and time‐variable (trait‐dependent and trait‐independent) diversification models, we examined changes in speciation and extinction rates through time in the Neotropics in relationship to other areas of the world, and estimated the time of Neotropical colonizations. Results We found that from the origin of lepidosaurs and mammals until the Pliocene (the Miocene for birds), diversification rates within the Neotropics were lower than rates in other regions (i.e., turnover was high). Afterwards, extinction decreased relative to speciation, and Neotropical diversification outpaced diversification in other regions. Dispersal out of the Neotropics also increased after the Pliocene (the Miocene for birds), exceeding into‐the‐Neotropics migrations. For amphibians, diversification rates in the Neotropics have been higher than in other areas through time, and dispersal out of the Neotropics decreased in the Cenozoic. Main conclusions The common view that the Neotropics are an ancient source of world species diversity, with high in situ speciation, dispersal to other areas and low extinction, might be true only for amphibians. For mammals, birds and lepidosaurs, the Neotropics acted as a diversity sink from their origin until the Miocene–Pliocene (i.e., diversification rates were lower and turnover higher than in other areas). Only afterwards did the region turn into a diversity source. Our study highlights that models accounting for rates of diversification that vary through time could improve our capacity to assess evolutionary dynamics over long time‐scales.

Experimental melting of phlogopite-peridotite in the garnet stability field - Pierre Condamine; Etienne Médard; Jean-Luc Devidal (Contributions to Mineralogy and Petrology, 2016)

Out of Himalaya: the impact of past Asian environmental changes on the evolutionary and biogeographical history of Dipodoidea (Rodentia) - Julie Pisano; Fabien L. Condamine; Vladimir Lebedev; Anna Bannikova; Jean‐Pierre Quéré; Gregory I. Shenbrot; Marie Pagès; Johan R. Michaux (Journal of Biogeography, 2015)
Aim We assessed the influence of past environmental changes, notably the importance of palaeogeographical and climatic drivers, in shaping the distribution patterns of Dipodoidea (Rodentia), the superfamily most closely related to the large species‐rich superfamily Muroidea ( c . 1300–1500 species). Dipodoids are suitable for testing several biogeographical hypotheses because of their disjunct distribution patterns in the Northern Hemisphere and the numerous species distributed in Asian deserts. Location Holarctic. Methods We inferred molecular phylogenetic relationships for Dipodoidea (34 out of 51 species and 15 out of 16 genera) based on five coding genes. A time‐calibrated phylogeny was estimated using a Bayesian relaxed molecular clock with four fossil calibrations. A cross‐validation procedure was adopted to examine the impact of each fossil on our estimates. The ancestral area of origin and biogeographical scenarios were reconstructed using time‐stratified dispersal–extinction–cladogenesis models. Results Phylogenetic analyses recovered a well‐resolved and supported topology. The divergence between Dipodoidea and Muroidea occurred in the late Palaeocene ( c . 57.72 Ma) and modern Dipodoidea diversified during the middle Eocene ( c . 40.62 Ma). Similar results were found with each calibration strategy used with the cross‐validation procedure. The reconstruction of ancestral areas and biogeographical events indicated that modern Dipodoidea originated in the Himalaya‐Tibetan and Central Asian region. Main conclusions At the time when Dipodoidea diversified (middle Eocene), the Central Asia and Himalaya‐Tibetan Plateau region experienced major uplift episodes due to the collision of India with Asia, which also induced diversification events in many other groups. Other important diversification events (e.g. divergence between Zapodidae and Dipodidae in Central Asia) took placed during the Eocene–Oligocene transition when the global temperature decreased significantly and rodent/lagomorph‐dominant faunas replaced Eocene perissodactyl‐dominant faunas. All of these climatic and geological disruptions in the Central Asia and Himalaya‐Tibetan Plateau region modified landscapes and offered new habitats that favoured diversification events, thus triggering the evolutionary history of Dipodoidea.